Kelimpahan dan Prevalensi Ektoparasit Ikan Kakatua (Famili Scaridae) di Pasar Ikan Kedonganan, Kabupaten Badung, Bali - Sitorus, Handayani; Julyantoro, Pande Gde Sasmita; Pebriani, Dewa Ayu Angga (Current Trends in Aquatic Science, 2020)
Existence of parrotfish in Bali, especially at Kedonganan fish market, Badung Regency are already familiar for local society and visitors. However, the research about parrotfish specifically about parasites is still scarce. One factor that cause the decrease of fish quality is diseases caused by the presence of parasites in the fish body. This study aims to determine the various types of ectoparasite, abundance, prevalence, relationship between length or weight and number of parasites in the parrotfish (Family Scaridae). The sample of research were collected from Kedonganan fish market, Badung Regency, Bali from November until Desember 2019. The research was used a descriptive methods with purposive sampling technique. Ectoparasites found in the 35 gills of parrotfish were Gnathia sp. (492 ind), Hatschekia sp. (156 ind), and Haliotrema sp. (1.186 ind). The highest ectoparasite abundance is Haliotrema sp. (33.88 ind/fish) while the highest ectoparasite prevalence was Gnathia sp. (80.00%) and belong to a “usually” of infection level. The correlation between the length and number of parasites is in the “medium” level with the value of correlation (r) was 0,460 while the correlation between the weight and number of parasites was in the “medium” level with the value (r) was 0.502.